Analysis of Translation Techniques, Methods, and Ideology on Children’s Bilingual Story Books - Niswatin Nurul Hidayati (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
Purpose - This research aimed to describe, the techniques, methods and ideology used by the author of children’s bilingual books. Design/methodology/approach - This study used descriptive qualitative in this research, in which the author used Molina & Albir and Newmark for the basic theory. Findings - The author found that the bilingual books' author mostly used literal translation as the technique. Then, for the methods, the most frequent was a word-for-word and literal translation. It meant that the author's ideology was foreignization because the bilingual books' author tended to maintain the word of the source language. Originality/value - The concluded that literal or word-for-word translation in translating stories for children is not suitable, since the sentences in the translated version tended to be complicated which is not suitable for teachers, parents, and children especially. The suggested for the bilingual books' authors use a communicative translation so that it can be easily read and understood. Paper type – Research paper